Productivity of Ground nut (Arachis hypogaea L.) in summer rice fallows under different frequencies of irrigation. - Muktha T M (Department of Agronomy, College of Horticulture, 1995)
A field experiment was conducted in the rice fallows of the Agricultural Research Station, Mannuthy during the summer season (February –May) of 1994 to identify a groundnut variety suitable for summer rice fallows and to find out the effect of different irrigation frequencies on the growth and yield of the crop. The experiment was laid out in split plot design with three replications. The main plot treatments were five frequencies of irrigation viz. no irrigation and irrigation at IW/CPE ratios of 0.25, 0.50 and 0.75 and 1.0. The subplot treatments were three varieties of groundnut viz. TG-3 Co-2 and VRI-3. Irrigation at closer intervals (IW/CPE ratios of 0.75 and 1.0) improved the growth characters like number of branches, leaf area index and dry matter production. Moisture stress during early growth stages delayed flowering and adversely affected nodulation. Yield attributes like number of pegs per plant, weight of pods per plant and shelling percentage were improved by higher frequencies of irrigation (IW/CPE ratios of 0.75 and 1.0). The highest pod yield (2408 kg/ha) was obtained when crop was irrigated at IW/CPE ratio of 1.0 which was on par with that at IW/CPE ratio 0.75 (2288 kg/ha). Even though irrigation did not significantly influence protein and oil content of kernels, protein yield and oil yield were influenced significantly. Among the varieties, especially during the rainfree period (upto 50 DAS) VRI-3 produced the highest number of branches, drymatter and number of nodules per plant. Leaf area index was highest for Co-2. However TG-3 showed an early flowering, higher yield attributes and thereby highest pod yield. The variety VRI-3 was on par with TG-3 in pod yield. TG-3 gave the highest protein yield whereas VRI-3 gave highest oil content and oil yield. The results indicated that among the different frequencies of irrigation IW/CPE ratio of 0.75 was the optimum as it gave higher pod yield with lesser quantity of water. Among the varieties TG-3 was the best followed by VRI-3 in terms of economic yield.